INDUSTRIAL LOCATION IN TRIPOLI AND BENGHAZI - El-Mehdawi, Dr. Mohamed El-Mehdawi (مجلة كلية الاداب, 1975)
According to the Industrial census of 1971, Tripoli and whazi were the most important industrial cities in Libya, rining about 73 percent of all the establishments with more Ton 10 workers, and employing about 84 percent of the total Torkers. The types of industries present in the two cities, che clements of their structure, and other considerations such as which has the more rapid growth and industrial expansion, are the concern of this study. The reason why Tripoli rather than Benghazi is called the industrial town of Libya becomes evident when the industrial structure of the two towns is examined. More factories are located within the contiguous area of Tripoli and, in addition, the establishments of Tripoli are larger and employ more people.